The method of optical investigations of the nanostructural diamond-like a-C:N films - Kara-Murza, S.V.; Belyaev, B.V.; Gritskih, V.A.; Zhikharev, I.V.; Kortchikova, N.V.; Naumenko, D.A.; Prudnikov, A.M. (Functional Materials, 2007)
A complex technique has been proposed for optical investigations of nanostructured diamond-like a—C:N films. To determine the thickness d, refractive index no and extinction coefficient n₀, the refraction ellipsometry at fixed wavelength λ₀ = 632.8 nm with different incidence angles has been used. Proceeding from the n₀, K₀ and d values, the n(λ), K(λ) dependences have been restored basing on the optical transmission curves within the 280-1200 nm range, and, as a consequence, the dependence of the imaginary part of dielectric constant, ξ", on the photon energy near the fundamental absorption edge. The band gap width Eg and the Tauc coefficient B have been determined for the films obtained under various technological conditions and preliminary conclusions have been drawn for the contributions from sp² and sp³ phases depending on those conditions.